2001
DOI: 10.1152/ajprenal.2001.280.4.f683
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation is probably not a prerequisite for renal interstitial fibrosis in normoglycemic obese rats

Abstract: We examined the role of inflammation in the development of renal interstitial fibrosis in Zucker obese rats, which rapidly present kidney lesions in the absence of hypertension and hyperglycemia. Type I and III collagens were quantified using a polarized light and computer-assisted image analyzer. The expression of mRNA encoding matrix components, adhesion molecules, chemokines, and growth factors was followed by RT-PCR. The presence of synthesized proteins as well as lymphocytes and macrophages was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
3
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
6
21
3
1
Order By: Relevance
“…However, we saw no evidence of insulitis in this model. In addition, in the ZDF model, early extracellular matrix remodeling in the kidney seems to be independent of any inflammatory process (37). Finally, hypertension in the ZDF rat may also contribute to activation of the RAS and potentially to progressive ␤-cell dysfunction in this model (38).…”
Section: Discussionmentioning
confidence: 87%
“…However, we saw no evidence of insulitis in this model. In addition, in the ZDF model, early extracellular matrix remodeling in the kidney seems to be independent of any inflammatory process (37). Finally, hypertension in the ZDF rat may also contribute to activation of the RAS and potentially to progressive ␤-cell dysfunction in this model (38).…”
Section: Discussionmentioning
confidence: 87%
“…The cells became elongated and were rearranged after a 3-h uniaxial stretching. The relationship between the number of cells and the cell angular direction in control static experiments or during (Lavaud et al 2001) Forward: 5′-TGCCCACAGCCTTCTACACCT-3′ 244 58 5 10 Reverse: 5′-CAGCCATTCCTCCCACTCCAG-3′ Tenascin-C (Shen et al 2001) Forward: 5′-CAGAAGCTGAACCGGAAGTTG-3′ 278 55 10 11 Reverse: 5′-GGCTGTTGTTGCTATGGCQCT-3′ GAPDH (Beeres et al 2006) Forward: 5′-TCCCTCAAGATTGTCAGCAA-3′ 308 55 10 12 Reverse: 5′-AGATCCACAACGGATACATT-3′ stretching is displayed in Fig. 4.…”
Section: Bmsc Number and Orientation Under Stretchingmentioning
confidence: 99%
“…In conclusion, in the absence of hypertensive or hyperglycemic disorders, the heart seems to display a sufficient line of defense against oxidative stress during the development of cardiac hypertrophy. left ventricular hypertrophy; renal failure; oxidative stress; Zucker rats; hyperlipidemia ZUCKER OBESE RATS develop, at 3 mo and onward, severe structural alterations of the kidneys and renal impairment, leading to renal failure in 9-mo-old animals (31,36,37,44,48,61). We have recently shown that these alterations are initiated in the absence of hypertension, diabetes, and inflammatory cell infiltration (37) but might derive from an oxidative stress in kidney tissue (48,49).…”
mentioning
confidence: 99%